Pitch and roll derivatives of a delta wing with curved leading edge in high speed flow - Ghosh, K; Murthy, M; Khan, Sher Afghan; Pandey, P K (AerosocietyofIndia, 1990)
Ghosh's unified similitude has been applied to oscillating delta wings of arbitrary plan forms in supersonic/ hyper- sonic flow. The quasi-steady derivative which was obtained by Ghosh for a hypersonic delta wing is extended to supersonic Mach number and curved leading edges. The unsteady moment derivative due to the incidence rate is obtained by combining Ghosh's unsteady theory and the quasi-steady theory. The results are compared with Hui et. al. The shock is assumed to be attached to the leading edge. The effects of viscosity and real gas have not been included.